2005
DOI: 10.1292/jvms.67.951
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological Survey of Feces from Feral Pigenons in Japan

Abstract: ABSTRACT. Some public areas in Japan such as parks and gardens can be highly contaminated with pigeon feces. We examined levels of four bacterial contaminations in fecal samples from feral pigeons in 7 prefectures. We isolated Salmonella Typhimurium and S. Cerro from 17 (3.9%) of 436 samples, as well as Mycobacterium spp. including M. avium-intracellulare complex from 29 (19.0%) of 153 samples. The polymerase chain reaction detected Chlamydia psittaci and C. pecorum in 106 (22.9%) of 463 samples, but E. coli O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
1
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 16 publications
2
47
1
4
Order By: Relevance
“…Pigeons could be able to carry many pathogenic virus, bacteria, fungus and protozoa for humans and animals without causing any diseases in themselves 1,5,7,10,16 . Domestic pigeons are one of the most important vehicle for spreading of zoonotic infections 16 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pigeons could be able to carry many pathogenic virus, bacteria, fungus and protozoa for humans and animals without causing any diseases in themselves 1,5,7,10,16 . Domestic pigeons are one of the most important vehicle for spreading of zoonotic infections 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Pigeons are potential reservoir for humans that host many of pathoİleti şim (Correspondence) +90 505 6056246 sinasia@gmail.com S14 The Potential Risk in ... 22 of pigeon cloacal swab samples taken from domestic pigeons, pigs, cattle and horses in their study. Tanaka et al 10 conducted the study concerning the isolation and idenfication of Salmonella spp., Mycobacterium spp., E. coli O157 and Chlamydia spp. and they detected the presence of these bacteria in the samples of pigeon feces that were taken from 38 diff erent public parks, located in 7 regions.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Tanaka et al found C. psittaci in 106 of 463 (22.9%; 95% CI, 19% to 27%) fecal samples obtained from feral pigeons. However, they did not use exclusively fresh fecal samples and applied a nested PCR protocol, which is known to be particularly prone to contamination (13).…”
mentioning
confidence: 99%
“…No Japão, os pombos encontram-se amplamente distribuídos nas áreas urbana e rural, e entram em contato com os seres humanos em parques, templos, santuários, jardins públicos e estações ferroviárias (Tanaka et al, 2005). Em Israel, a presença dessas aves tem sido relatada apenas em parques urbanos (Shwartz et al, 2008).…”
Section: Pombo Doméstico (Columba Livia)unclassified
“…com capacidade de infectar o homem foi relatada em várias análises de fezes de pombos de vida livre em diferentes países do mundo. Há registros de isolamento de Salmonella enterica sorotipo Typhimurium, patógeno responsável por inúmeros surtos de infecção alimentar humana desde a década de 1960de (Lee, 1974 na Bélgica (Pasmans et al, 2004), no Japão (Tanaka et al, 2005), na Croácia (Vucemilo et al, 2003), em Trinidad (Gopee et al, 2000) e em Barcelona (Casanovas et al, 1995).…”
Section: Pombo Doméstico (Columba Livia)unclassified